Historical distribution of kelp forests on the coast of British Columbia: 1858–1956. (July 2020) - Costa, Maycira; Le Baron, Nicole; Tenhunen, Kim; Nephin, Jessica; Willis, Peter; Mortimor, James P.; Dudas, Sarah; Rubidge, Emily
Abstract: The quantification of kelp forest distribution across space and time is critical to support decision-makers responsible for habitat management and conservation. Spatial data such as aerial photos and satellite imagery are key for deriving kelp distribution; however, they have only become available at an adequate quality within the 20th and 21st centuries. In this study, British Admiralty (BA) charts created between 1858 and 1956 covering the British Columbia coast and portions of the adjacent Washington and Alaska coast were used to create a digital historical baseline map of kelp presence. A total of 137 BA charts were scanned at 200 DPI, georeferenced, and kelp features were manually digitized following a rigorous method considering the scale and quality of the data. An accuracy assessment of the digitized kelp features concluded that 99% of the kelp features occurred in expected areas within a depth of less than 40 m, and only about 1% of the features occurred entirely outside of this depth. Recently mapped kelp forests in similar areas reaffirmed the results of the produced baseline map. Potential sources of uncertainty should be considered when working with the historic BA charts such as the surveyor's method for defining floating kelp features, the artistic ability of the cartographer when transcribing the information from the surveys to the BA charts, and the regional seasonality of kelp cover. The outcome of this research shows that the historical BA charts are an unconventional but extremely rich source of baseline coastal habitat data from the 19th century. The methods conducted are simple and robust and could be applied to other regions where historical charts with sufficient quality exist. Highlights: British Admiralty charts created between 1858 and 1956 covering the British Columbia coast and portions of the adjacent Washington and Alaska coast were used to create a digital historical baseline map of kelp presence. An accuracy assessment of the digitized kelp features concluded that 99% of the kelp features occurred in expected areas within a depth of less than 40 m, and only about 1% of the features occurred entirely outside of this depth. The outcome of this research shows that the historical BA charts are an unconventional but extremely rich source of baseline coastal habitat data from the 19th century.